Structural geology and tectonic history of the Taku Schist and surrounding units, NE Peninsular Malaysia / Muhammad Afiq Md Ali - Muhammad Afiq , Md Ali (2018)
Recent studies in SE Asia have focused on extensional detachments following the Indosinian Orogeny, which have not as yet been described in Peninsular Malaysia. In this context, the study demonstrates the structural evolution of the Taku Schist with emphasis on kinematics of shear deformation by way of field and microstructural observations to explain the regional tectonic evolution of NE Peninsular Malaysia. The Taku schist represents an original Paleozoic sedimentary succession metamorphosed to amphibolite facies during Indosinian Orogeny. This is indicated by an episode of burial and metamorphism (D1), followed by top-WSW directed flattening (D2) and lastly by upright folding (D3). The overall orogenic structure by E-W directed contraction is in agreement with the evolution of continental subduction and the collision of Sibumasu and Indochina during Permo-Triassic times. For the first time, a top-SE directed shear deformation (D4) was documented, resulting in the formation of a core complex and a large-scale extensional detachment. The observed low-angle mylonitic detachment shearing is accommodated by later normal and strike-slip faulting, which forms a major NNW-SSE trending fault zone. The deformation is accompanied by greenschist-facies retrograde metamorphism, synchronous with the major exhumation of the Taku Schist and other footwall units. This includes the Stong Complex, Kemahang Granite and the Tiang Schist, separated from the Gua Musang hanging-wall by a similar top-SE detachment mechanism. The syn-kinematic intrusion of the high temperature Stong Complex during top-SE shearing and formation of young sedimentary basins in the hanging-wall indicate that the post-orogenic extension and concurrent exhumation likely occurred during Late Cretaceous – Eocene time.